Subcellular Localization of Rice Acyl-CoA-Binding Proteins ACBP4 and ACBP5 Supports Their Non-redundant Roles in Lipid Metabolism - Liao, Pan; Leung, King Pong; Lung, Shiu-Cheung; Panthapulakkal Narayanan, Saritha; Jiang, Liwen; Chye, Mee-Len (Frontiers in Plant Science, 2020)
Acyl-CoA-binding proteins (ACBPs), conserved at the acyl-CoA-binding domain, can bind acyl-CoA esters as well as transport them intracellularly. Six ACBPs co-exist in each model plant, dicot Arabidopsis thaliana (thale cress) and monocot Oryza sativa (rice). Although Arabidopsis ACBPs have been studied extensively, less is known about the rice ACBPs. OsACBP4 is highly induced by salt treatment, but down-regulated following pathogen infection, while OsACBP5 is up-regulated by both wounding and pathogen treatment. Their differential expression patterns under various stress treatments suggest that they may possess non-redundant functions. When expressed from the CaMV35S promoter, OsACBP4 and OsACBP5 were subcellularly localized to different endoplasmic reticulum (ER) domains in transgenic Arabidopsis. As these plants were not stress-treated, it remains to be determined if OsACBP subcellular localization would change following treatment. Given that the subcellular localization of proteins may not be reliable if not expressed in the native plant, this study addresses OsACBP4:GFP and OsACBP5:DsRED expression from their native promoters to verify their subcellular localization in transgenic rice. The results indicated that OsACBP4:GFP was targeted to the plasma membrane besides the ER, while OsACBP5:DsRED was localized at the apoplast, in contrast to their only localization at the ER in transgenic Arabidopsis. Differences in tagged-protein localization in transgenic Arabidopsis and rice imply that protein subcellular localization studies are best investigated in the native plant. Likely, initial targeting to the ER in a non-native plant could not be followed up properly to the final destination(s) unless it occurred in the native plant. Also, monocot (rice) protein targeting may not be optimally processed in a transgenic dicot (Arabidopsis), perhaps arising from the different processing systems for routing between them. Furthermore, changes in the subcellular localization of OsACBP4:GFP and OsACBP5:DsRED were not detectable following salt and pathogen treatment, respectively. These results suggest that OsACBP4 is likely involved in the intracellular shuttling of acyl-CoA esters and/or other lipids between the plasma membrane and the ER, while OsACBP5 appears to participate in the extracellular transport of acyl-CoA esters and/or other lipids, suggesting that they are non-redundant proteins in lipid trafficking.